Pengaruh Carbon Emission Disclosure Terhadap Kinerja Keuangan Perusahaan dengan Dewan Komisaris Independen Sebagai Variabel Moderasi (Studi Pada Perusahaan Sub Sektor Konstruksi Berat yang Terdaftar di BEI Periode 2021-2023) - Afaza, Andi Muhammad Fardan Adhe; Fitriasari, Rizka (CV. Green Publisher Indonesia, 2025)
This study aims to provide empirical evidence on the effect of carbon emission disclosure on corporate financial performance, with the role of independent commissioners as a moderating variable. The research is motivated by the increasing pressure on companies to enhance environmental transparency while maintaining financial performance, particularly in environmentally sensitive industries. The population of this study consists of heavy construction sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. Using a purposive sampling technique, 10 companies were selected, resulting in a total of 30 firm-year observations. The study employs secondary data obtained from annual reports and sustainability reports, which reflect both financial indicators and carbon emission disclosure practices. Data analysis was conducted using Moderated Regression Analysis (MRA) with the assistance of IBM SPSS Statistics 25. The results indicate that carbon emission disclosure has a significant negative effect on corporate financial performance, suggesting that disclosure-related costs and compliance efforts may outweigh short-term financial benefits. Furthermore, independent commissioners are found to weaken the relationship between carbon emission disclosure and financial performance; however, this moderating effect is statistically insignificant. These findings imply that the presence of independent commissioners has not yet played an optimal role in balancing environmental responsibility and financial objectives. This study contributes to the literature on environmental accounting and corporate governance and provides practical insights for regulators and companies in designing more effective sustainability and governance strategies.